Promoting Student’s Literacy Skills by Infusing Technology as Literacy Instruction in Reading and Writing Class - Paramita Dharmayanti, Putu Ayu; Ari Wiryadi Joni, Dewa Ayu (Program Studi Pendidikan Bahasa Inggris FKIP Universitas Mahasaraswati Denpasar, 2023)
The use of technology in the classroom is crucial to introducing students to the use of technology and enhancing student literacy, particularly digital literacy. The article demonstrates how to incorporate technology into lessons to help kids become more literate. This study was conducted as literature study that has 5 stages to be completed that are formulating the research questions, looking for the literatures, examining the inclusion, assessing the primary research, processing the data, and interpreting the data. Based on the literature study that has been done, SAMR model and TPACK model are appropriate model to infuse technology into literacy classroom. Regarding to literacy classroom, SAMR model focus on the effect of integrating technology into literacy classroom by dividing the integration into some levels, they are Substitution, Augmentation, Modification, and Redefinition. However, TPACK focuses on how technology is integrated in the learning content and also teaching pedagogy.